Wedding Cost: Multiservice Ijarah Financing Mechanism at BMT NU Kediri City - Khairan, Khairan; Badriyah, Qurotul (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This study aims to explain the mechanism of marriage financing with a multiservice Ijarah contract at BMT NU Kediri City. The research method is qualitative, using a case study approach, and it is supported by primary and secondary data. Data collection through interview, observation, and documentation methods are analyzed by condensation, display, and conclusion methods and validated by data and source triangulation methods. The mechanism of marriage financing at BMT NU Kediri City is a form of cooperation between the customer and BMT NU, through a multiservice Ijarah financing contract with several stages, such as; The customer applies for financing to BMT NU Kediri City through financing analysis with the 5C principle, The customer goes to the BMT office with the husband or wife/guardian as a witness, The customer brings administrative requirements, The customer signs the note, and the customer receives the disbursement of funds by the specified. The purpose of this financing is to facilitate financing customer's Ijarah multiservice.